Reforms of the social protection systems in Bosnia and Herzegovina - Buljubašić, Suada (Ревија за социјална политика/Journal of Social Policy, 2018)
Reforms of the social protection system in Bosnia and Herzegovina are essential for several reasons. The existing laws have been outdated and incompatible with ratified conventions and other international documents and domestic regulations. Through the process of Bosnia and Herzegovina’s accession to the European Union, reform activities in the field of social protection have been intensified due to the responsibilities taken over by the State and its entities to harmonize the existing regulations with international conventions and European standards in this field as well. Reform activities are reflected in the harmonization of existing regulations and the adoption of new ones in order to regulate this area. In the reform activities initiated so far, transformation and deinstitutionalization of social protection institutions is of particular importance. These reforms are aimed at increasing the quality of life by respecting the highest standards of children’s rights, disabled people and the elderly through the development of community services as an alternative to institutional protection. Given this fact, within the framework of the reform processes, the Strategy for Deinstitutionalization and Transformation of Social Protection Institutions in the Federation of Bosnia and Herzegovina (2014-2020) and the FBIH Law on Foster Care have been adopted. The aim of these reforms is to reduce the placement of children and adults in the institutions and increase the exit from institutions by stimulating family re-integration and appropriate community support. Within the framework of the reform processes, there are activities that have been initiated to enact legislation which shall define the activities of social work, determine the minimum professional conditions for the work of professional workers, establish the standards and procedure for accreditation of training programs for professional workers in social protection and licensing of professional workers. Additionally, it has been necessary to define and standardize social rights and services, as well as to standardize the existing services and introduce the new ones. In order to regulate this area in accordance with European standards, the two laws, namely the Law on Social Work and the Law on Social Services, have already been enacted and submitted to the Parliamentary procedure.
Keywords: Bosnia and Herzegovina; social protection reforms; Deinstitutionalization; transformation of social protection institutions